DAMPAK PELATIHAN REGULASI EMOSI ANAK (REMONA) TERHADAP PERILAKU DISRUPTIF PADA SISWA KELAS I SD KY AGENG GIRI MRANGGEN KABUPATEN DEMAK - AMALIA, SITI; Ediati, Annastasia (Empati, 2017)
This study aims to determine the impact of training "REMONA" regulation of emotion of children against disruptive behavior in class I elementary school Ky Ageng Giri. This research method uses pre-experimental design of the one group prestest posttest design that is research using one group of research sample and conducted measurement or observation (pre and posttest design) before and after given treatment. Subjects in this study that is all students class I SD Ky Ageng Giri as many as 32 children. Sampling technique in this research is saturated sampling, the entire population is sampled. Data analysis on the research using Paired Sample T-test The results showed that "REMONA" training was significantly effective in reducing disruptive behavior in grade I students of elementary school Ky Ageng Giri with disruptive behavior score score score before "REMONA" training (Mpretest = 18,78 ; SDpretest = 14,397) and after training (MposttestI = 10.31; SDposttestI = 7,168) with p <0.001. Even evaluated after one week, training "REMONA" remained effective in reducing disruptive behavior (MposttestII = 10.03; SDposttestII = 6,684).Â Â Â